Gestión y costos de producción: Balances y perspectivas: Management and production costs: Balances and perspectives - Casanova Villalba, César Iván; Núñez Liberio, Rosa Verónica; Navarrete Zambrano, Cecilia Mercedes; Proaño González, Esther Angélica (Revista de Ciencias Sociales, 2021)
Companies are obliged to constantly compete, and in order to remain in the market, they must manage production costs by generating strategies that contribute to correct decision-making. The research aims to present a theoretical view of production cost management based on activity costing, with descriptive, documentary analysis methodology, referring to the genealogy of production management and costs. The result of the study is a dynamic between the perspectives of the actors according to the management that is carried out on production costs, together with an analysis of the costing systems under the information approach for decision making, leaving the system of ABC costing as a method that presents more accurate data on indirect costs. It is concluded that management and production costs are closely linked in their execution and mutually depend on the perspectives and data obtained from the balance sheets..